THE PRACTICAL ACCOUNTING INFORMATION SYSTEM TO CONTROL AND TO MAINTAIN THE FUND EFFECTIVELY AT FOREIGN COMPANY (BASED ON A CASE STUDY) - Sera Marettini (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2006)
The writer has observed how to maintain and to control cash effectively at one of foreign companies in Surabaya. It is applied for one of the companies which has a head office in the United States of America. The head office controls all financial things in Indonesia’s company due to the size of branch in Indonesia. The head office itself has many branches almost worldwide. There are some constraints to control the cash maintenance in this case; since a final controlling role will be performed by the head office and an executor role will be performed by the branch, and both of them are separated for thousand miles away, no available on-line accounting system and the branch is not allowed to have a bank account by itself, the only similar thing is they utilize the same program for accounting system. The PCs used in the branch are stand-alone computers. Herewith the writer would like to share an applied system to minimize the mistakes and to smoothen the cash maintenance and control.